The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13613-019-0485-z
|View full text |Cite
|
Sign up to set email alerts
|

Photoplethysmographic determination of the respiratory rate in acutely ill patients: validation of a new algorithm and implementation into a biomedical device

Abstract: BackgroundRespiratory rate is among the first vital signs to change in deteriorating patients. The aims of this study were to evaluate the accuracy of respiratory rate measurements using a specifically dedicated reflection-mode photoplethysmographic signal analysis in a pathological condition (PPG-RR) and to validate its implementation within medical devices.MethodsThis study is derived from a data mining project, including all consecutive patients admitted to our ICU (ReaSTOC study, ClinicalTrials.gov identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…In daily practice, this parameter may not be adequately recorded. 18 Recently, L'Her et al 19 demonstrated that breathing frequency could be obtained from photoplethysmography tracings. The breathing frequency derived from pulse oximetry signals correlated very well with breathing frequency measured manually, even in subjects with atrial fibrillation.…”
Section: Breathing Frequencymentioning
confidence: 99%
See 3 more Smart Citations
“…In daily practice, this parameter may not be adequately recorded. 18 Recently, L'Her et al 19 demonstrated that breathing frequency could be obtained from photoplethysmography tracings. The breathing frequency derived from pulse oximetry signals correlated very well with breathing frequency measured manually, even in subjects with atrial fibrillation.…”
Section: Breathing Frequencymentioning
confidence: 99%
“…The breathing frequency derived from pulse oximetry signals correlated very well with breathing frequency measured manually, even in subjects with atrial fibrillation. 19 This function has been incorporated into some automated oxygen titration and weaning systems, enabling the continuous measurement of breathing frequency in patients wearing a pulse oximetry device. 19…”
Section: Breathing Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal images [9][10][11] measure the temperature variations between inhalation and exhalation phases with it not working if the nasal area is not visible. In recent years, several works have used the photoplethysmography technique, employed initially to measure cardiac frequency [12], to measures skin blood changes to track RR [13][14][15][16][17][18]. Some works such as [18] train a CNN using respiratory raw signal as reference and a skin reflection model to represent the color variations of the image sequence as input.…”
Section: Introductionmentioning
confidence: 99%